The Composition, Antioxidant and Antibacterial Activity of Essential Oils from Five Species of the Magnoliaceae Family - Yang, Dandan; Ma, Daocheng; Song, Ziqi; Yang, Mei; Xu, Yuanyuan (Molecules (Basel, Switzerland), 2024)
The leaves of Magnoliaceae family plants contain abundant essential oils (EOs), and these species can be used in many fields due to their high industrial, medicinal, and ornamental values. This study aims to identify the main compounds of the EOs from the leaves of five common Magnoliaceae species (Michelia maudiae, Michelia hedyosperma, Michelia macclurei, Manglietia lucida, Manglietia conifer) using hydrodistillation, GC–MS analysis, and in vitro tests. Additionally, the antioxidant and antibacterial activities of the EOs were also evaluated. The results show that 151 compounds were identified across five species, with sesquiterpenes being dominant. Some key compounds (such as β-caryophyllene, δ-amorphene, β-guaiene, globulol, and β-acorenol) were common among all the species, highlighting their crucial roles in plant physiology and resilience. Other compounds (like valeranone and nerolidol in M. maudiae and β-elemene in M. macclurei) were specific, indicating different functions. Among the five species, the essential oil of M. macclurei contains β-elemene and nerolidyl acetate, and it has the weakest antioxidant activity (IC50 value: 2918.61~21,341.98 μg/mL) but the strongest antibacterial activity (inhibition zone diameter: 8.55 ± 0.93~22.92 ± 0.46 mm; LC50 value: 0.02~0.78 mg/mL). Meanwhile, the EO of M. maudiae demonstrated the best antioxidant activity (the IC50 value was 1283.58~6258.32 μg/mL) and the second-best antibacterial activity (the inhibition zone diameter ranged from 7.61 ± 0.02 to 26.92 ± 0.46 mm, and the LC50 value was 0.03~2.28 mg/mL). Overall, the EO of M. maudiae had the best comprehensive performance. Therefore, the EOs of M. macclurei and M. maudiae showed different performances in biological activity categories, and they could be developed and used in different fields, with the possibility of discovering new applications. This brings inspiration to the potential commercial and industrial uses of sesquiterpenes in Magnoliaceae.